Fibre optic active components and devices. Package and interface standards. Design guidelines of electrical interface of PIC packages using silicon fine-pitch ball grid array (S-FBGA) and silicon fine-pitch land grid array (S-FLGA) Part 21, (15th June 2021) - British Standards Institution,
No abstract available